2010
DOI: 10.1242/jcs.069153
|View full text |Cite
|
Sign up to set email alerts
|

Kinectin-mediated endoplasmic reticulum dynamics supports focal adhesion growth in the cellular lamella

Abstract: SummaryFocal adhesions (FAs) control cell shape and motility, which are important processes that underlie a wide range of physiological functions. FA dynamics is regulated by cytoskeleton, motor proteins and small GTPases. Kinectin is an integral endoplasmic reticulum (ER) membrane protein that extends the ER along microtubules. Here, we investigated the influence of the ER on FA dynamics within the cellular lamella by disrupting the kinectin-kinesin interaction by overexpressing the minimal kinectin-kinesin i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 65 publications
2
42
0
Order By: Relevance
“…Based on previous antecedents showing that PTP1B is positioned over peripheral paxillin adhesions by tubular extensions of the ER (Hernández et al, 2006), and that peripheral adhesions targeted by ER tubules subsequently grew in size (Zhang et al, 2010), we hypothesized that PTP1B on the surface of the ER could regulate adhesion lifetime during cell protrusion. We tested this hypothesis in immortalized fibroblasts derived from PTP1B-deficient mouse (KO cells) (Haj et al, 2002) transfected with mRFP-paxillin to label adhesions, and either GFP-PTP1B wild type (WT) or GFP-PTP1B (CS), a catalytically inactive mutant with the essential cysteine 215 substituted by serine (Guan and Dixon, 1991;Flint et al, 1997).…”
Section: Er-bound Ptp1b Regulates Adhesion Lifetimes During Lamellar mentioning
confidence: 96%
“…Based on previous antecedents showing that PTP1B is positioned over peripheral paxillin adhesions by tubular extensions of the ER (Hernández et al, 2006), and that peripheral adhesions targeted by ER tubules subsequently grew in size (Zhang et al, 2010), we hypothesized that PTP1B on the surface of the ER could regulate adhesion lifetime during cell protrusion. We tested this hypothesis in immortalized fibroblasts derived from PTP1B-deficient mouse (KO cells) (Haj et al, 2002) transfected with mRFP-paxillin to label adhesions, and either GFP-PTP1B wild type (WT) or GFP-PTP1B (CS), a catalytically inactive mutant with the essential cysteine 215 substituted by serine (Guan and Dixon, 1991;Flint et al, 1997).…”
Section: Er-bound Ptp1b Regulates Adhesion Lifetimes During Lamellar mentioning
confidence: 96%
“…33,34 Kinesin binds to the ER transmembrane protein kinectin and interfering this binding produces the collapse of the peripheral ER. 35,36 In neurons, microtubule-dependent localization of ER-bound PTP1B at the peripheral region of axonal growth cones is critical for Src activation and filopodia stability. 3 In migrating fibroblasts, the ER network extends toward the leading edge, positioning GFP-PTP1B over new adhesions assembled at the advancing lamella ( Fig.…”
Section: Microtubules Contribute To Position Er-bound Ptp1b At the Lementioning
confidence: 99%
“…Various studies have shown the involvement of endoplasmic reticulum (ER) transport in adhesion dynamics during cell migration (Burdisso et al, 2013;Yang et al, 2009;Zhang et al, 2010). ER is transported along microtubules (MTs) to the cell periphery by the tip-attachment complex (TAC) and sliding mechanisms (Friedman et al, 2010;Terasaki et al, 1986;Waterman-Storer and Salmon, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…ER is transported along microtubules (MTs) to the cell periphery by the tip-attachment complex (TAC) and sliding mechanisms (Friedman et al, 2010;Terasaki et al, 1986;Waterman-Storer and Salmon, 1998). Disruption of either ER transport mechanism has been shown to reduce cell migration Zhang et al, 2010). The sliding mechanism is mediated by the microtubule (MT) motor protein kinesin-1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation